2010
DOI: 10.1007/s00208-010-0568-5
|View full text |Cite
|
Sign up to set email alerts
|

Equidistribution of Heegner points and ternary quadratic forms

Abstract: We prove new equidistribution results for Galois orbits of Heegner points with respect to single reduction maps at inert primes. The arguments are based on two different techniques: primitive representations of integers by quadratic forms and distribution relations for Heegner points. Our results generalize an equidistribution result with respect to a single reduction map established by Cornut and Vatsal in the sense that we allow both the fundamental discriminant and the conductor to grow. Moreover, for fixed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Michel [30,Theorem 3] proved a "sparse" equidistribution version of (1.3), where G K can be replaced by any subgroup G < G K of index ≤ D 1/2115 . Related equidistribution problems were studied in [6,22,34].…”
mentioning
confidence: 99%
“…Michel [30,Theorem 3] proved a "sparse" equidistribution version of (1.3), where G K can be replaced by any subgroup G < G K of index ≤ D 1/2115 . Related equidistribution problems were studied in [6,22,34].…”
mentioning
confidence: 99%
“…Given such a reduction map, it is expected that the Galois orbits in CM(G, H) tend to be equidistributed among the finitely many fibres of the reduction map red. Such equidistribution results are already known in various cases [4,11,12,14,18] and were crucial in the proof of Mazur's non-vanishing conjecture by the first author and Vatsal [3,5,21].…”
Section: Introductionmentioning
confidence: 85%
“…This question was studied by a number of authors (cf. [5] and [10]). It turns out that the reduction map is not always surjective and is not in general one-to-one.…”
Section: Introductionmentioning
confidence: 99%
“…They proved that for d sufficiently large, the image of the reduction map is surjective and furthermore that it is equidistributed across all supersingular elliptic curves. A slight modification of this was investigated by Jetchev and the second author [10], where it was shown that the reduction from curves with exact CM by O d is surjective for d sufficiently large but not necessarily fundamental (albeit with some minor restriction on the choice of d). The approach taken in [5] and [10] was to use a correspondence between elliptic curves with CM by O d which reduce to a supersingular elliptic curve and optimal embeddings of O d in its endomorphism ring; roughly speaking, if O d embeds into the quaternionic order, then O dr 2 also embeds by multiplying by r, and optimal embeddings are those which do not come from smaller discriminants.…”
Section: Introductionmentioning
confidence: 99%